2022
DOI: 10.3390/ijerph19063297
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of Telehealth-Based Resistance Exercise Training in Adolescents with Cystic Fibrosis and Glucose Intolerance

Abstract: The aims of this study were to (1) determine the feasibility of a home-based resistance exercise training (RET) program in patients with cystic fibrosis and impaired glucose tolerance using virtual personal training and (2) observe the effects completion of the RET program had on glucose metabolism, pulmonary function, body composition, and physical fitness. The feasibility of the program was defined as 80% compliance. Ten participants (15.80 ± 2.20 yr, 25.1 ± 7.4 kg/m2) began a home-based resistance training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…The current pilot study and outcome measures were secondary, derived from a larger study investigating the feasibility and effects of home-based resistance exercise training in adolescents with CF and impaired glucose tolerance [ 36 ]. Adolescents aged 10 to 18 years with CF and pancreatic insufficiency were invited to participate in this prospective study.…”
Section: Methodsmentioning
confidence: 99%
“…The current pilot study and outcome measures were secondary, derived from a larger study investigating the feasibility and effects of home-based resistance exercise training in adolescents with CF and impaired glucose tolerance [ 36 ]. Adolescents aged 10 to 18 years with CF and pancreatic insufficiency were invited to participate in this prospective study.…”
Section: Methodsmentioning
confidence: 99%
“…25 Since the coronavirus disease 2019 pandemic, there has been a rapid increase in telehealth availability and this may serve as a useful adjunct to improve adherence and clinical outcomes for pwCF. 32 33 Similarly, the use of internet-based programs to increase participation of pwCF with exercise and physical activity has been trialed, albeit with varied success. 34 35 It is likely that there is a no “one-size fits all” approach to improving adherence to exercise and physical activity recommendations for pwCF and that an individualized, multifaceted approach is required.…”
Section: Exercise In Cystic Fibrosismentioning
confidence: 99%
“…Telehealth refers to the delivery of remote health care via communication technologies such as telephone calls, video calls, or text messaging. 10 In an era of advancing healthcare technology and access to telehealth, providing a supervised telehealth exercise program to this population could be a way to deliver exercise interventions to this population. This would minimize risks of cross-infection, and increase access to this important intervention for those who are geographically remote.…”
Section: Introductionmentioning
confidence: 99%
“…Recent single-arm trials with small sample sizes in adolescents and young adults with CF concluded that completing a supervised exercise program via video conferencing was feasible and acceptable to participants. 10,14 However, participation rates and compliance to the exercise interventions were variable and the studies did not report the involvement of end users in the design process. A randomized controlled trial comparing web-based physical activity promotion versus usual care in 107 adolescents and young adults with CF following hospital discharge demonstrated low uptake of the intervention and no between-group differences in changes in physical activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation